(untitled) (Research, Society and Development, 2024)
The objective of this study was to describe the clinical-epidemiological profile of patients with chronic kidney disease (CKD) on dialysis treated at the Pinheiro Hemodialysis Center in the State of Maranhão, through the analysis of medical records. It is a cross-sectional study, based on 204 medical records of patients who started treatment between August 2020 to August 2022. The most affected population group was male (63.2%), mixed race (80.9%), single (33.3%) and with low education (51%). There was a predominance of patients from other municipalities (77%). The most common age group at the onset of Hemodialysis (HD) was 35-59 (48%). Deaths occurred mainly in the age group over 60 years old (50%). Most patients were on HD for 1-5 years (71.1%). Arteriovenous fistula (AVF) creation occurred within 1 year for 57.6% of patients. 40.2% waited up to 1 year to start dialysis in other municipalities, until they were able to transfer to Pinheiro. A significant percentage of patients (94.6%) started HD via catheter, but the AVF is already the vascular access for 57.8%. Catheter infection was quite significant, at 88.7%. The majority have negative serology (95.1%). The underlying pathology that stood out the most was Diabetes Mellitus (DM) with 41.2% and the comorbidity Systemic Arterial Hypertension (SAH) accounted for 44.3%. The main diseases causing kidney disease in the population studied were diabetes and hypertension, morbid conditions that can be treated in basic health care, showing that there is a need for improvement in health policies in the various municipalities of Baixada Maranhão.